A micromechanical model for predicting biaxial tensile moduli of plain weave fabric composites. (July 2017) - Bai, JB; Xiong, JJ; Shenoi, RA; Wang, Q
This article presents a new micromechanical model to predict biaxial tensile moduli of plain weave fabric composites by considering the interaction between the orthogonal interlacing strands. The two orthogonal yarns in micromechanical unit cell were idealized as curved beams with a path depicted using sinusoidal shape functions. The biaxial tensile moduli of plain weave fabric composites were derived by means of the minimum total complementary potential energy principle founded on micromechanics. Biaxial tensile tests were conducted on the resin transfer molding–made EW220/5284 plain weave fabric composites at five biaxial loading ratios of 0, 1, 2, 3 and ∞ to validate the new model. Predictions from the new model were compared with experimental data. Good correlation was achieved between the predictions and actual experiments, demonstrating the practical and effective use of the proposed model. Using the new model, the biaxial tensile moduli of plain weave fabric composites can be predicted based only on the properties of basic woven fabric.